Mathematical Modeling of the Process of Acid Rain Formation in Case of Emissions from Thermal Power Plants - Biliaiev, M. M.; Petrenko, V. D.; Biliaieva, V. V.; Berlov, O. V.; Zvonarova, O. V. (Science and Transport Progress, 2024)
Purpose. It is known that acid rain has a negative impact on the environment. The formation of acid precipitation in the atmosphere occurs as a result of the chemical interaction of fuel combustion products and atmospheric humidity. Acid rain leads to crop losses, deterioration of soil fertility, and acidification of water in reservoirs. The development of scientifically based methods for studying the intensity of such acidic pollution of the air and soil surface in regions with significant emissions from thermal power plants remains an urgent problem. To solve this problem, it is important to use mathematical modeling, since it is impossible to determine the impact of emissions from thermal power plants on the formation of acid rain experimentally. Therefore, the main goal of the work is to create a mathematical model for predicting the formation of acid rain in the event of emissions from thermal power plants. Methodology. To predict the process of acid rain formation, a three-dimensional equation of convective diffusion transport of a pollutant is used, which takes into account the wind speed profile, atmospheric stratification, emission intensity of an impurity, and wind direction. This equation is also used to describe the process of water vapor transport in atmospheric air. To describe the process of acid formation in atmospheric air, a stoichiometric relationship is used. The numerical integration of the modeling equation of transfer was carried out using the splitting method. Findings. A multifactorial numerical model was built that allows determining the zones where acid rain is formed. The problem of predicting the formation of acid rain in the case of emissions from thermal power plants on the basis of the constructed numerical model is considered. Originality. A numerical model is proposed to predict the occurrence of acid rain due to emissions from thermal power plants. The model is multifactorial and takes into account convection, atmospheric diffusion, and an uneven wind profile. A computer code has been created that allows for rapid assessment of acid pollution zones. Practical value. The developed computer code for analyzing the zones of acidic pollution of the environment in the case of industrial emissions makes it possible to predict the intensity of such pollution in various meteorological conditions.